The Impact of Depositary Receipts on Stock Market Development: Evidence from Organization of Islamic Cooperation Stock Markets - Ibrahim, Norhazlina; Bacha, Obiyathulla Ismath; Ibrahim, Mansor H.; Abdul Wahab, Hishamuddin (International Journal of Economics and Financial Issues, 2020)
The issue of liquidity and the under development of the Organization of Islamic Cooperation (OIC) stock markets have been a hindrance factor for companies in those countries to seek fund and capital. Due to this reason, many companies choose Depositary Receipts (DRs) to raise capital internationally. Thus, this study aims at examining the financial implications of cross listing via the existing Depositary Receipts (DRs) on stock market development. This study employs a dynamic panel model covers sample of 146 firms from 17 OIC countries that are cross-listed as American Depositary Receipts (ADRs) or Global DRs from 1993 to 2016. The findings reveal that growth and expansion of international cross listings via DRs have a positive impact on domestic stock market. This study provides insights to OIC stock markets that consider accommodating Islamic Depositary Receipts (IDRs) in the future. Keywords: Depositary Receipts (DRs), stock market development, OIC countries, Islamic Finance JEL Classifications: G1, G10, 016 DOI: https://doi.org/10.32479/ijefi.9572